INTERVIEW OF CHIEF EDITOR OF SCIENTIFIC AND TECHNICAL JOURNAL «CASTING AND METALLURGY», CHAIRMAN OF COUNCIL BELOLIM, LAUREATE OF STATE-PRIZE OF RB, DOCTOR OF TECHNICAL SCIENCES, PROFESSOR D. M. KUKUJ WITH DIRECTOR OF OAO «MOGILEV METALLURGICAL PLANT» A. V. VOLKOV - D. M. Kukuj; A. V. Volkov (Литьë и металлургия, 2010)
.